2022
DOI: 10.7759/cureus.24895
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis: Therapeutic Strategies on the Horizon

Abstract: Multiple sclerosis (MS) is a chronic disease affecting the brain and the spinal cord. It is a chronic inflammatory demyelinating disease of the central nervous system. It is the leading cause of non-traumatic disability in young adults. The clinical course of the disease is quite variable, ranging from stable chronic disease to rapidly evolving debilitating disease. The pathogenesis of MS is not fully understood. Still, there has been a rapid shift in understanding the immune pathology of MS away from pure T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 177 publications
0
3
0
Order By: Relevance
“…MS is an autoimmune disorder associated with the demyelination of neurones in the brain and spinal cord [ 56 ]. The most common presentation shows a relapsing/remitting pattern, but some patients present with a more severe form of primary progressive disorder.…”
Section: Multiple Sclerosis (Ms)mentioning
confidence: 99%
“…MS is an autoimmune disorder associated with the demyelination of neurones in the brain and spinal cord [ 56 ]. The most common presentation shows a relapsing/remitting pattern, but some patients present with a more severe form of primary progressive disorder.…”
Section: Multiple Sclerosis (Ms)mentioning
confidence: 99%
“…The spinal cord microglia model demonstrated that propranolol treatment decreases interleukins’ production and frequency of spinal cord Th17 cells, enhancing MBP expression [ 55 , 198 ]. Furthermore, propranolol improved functional disability, tremors, and ataxia in multiple sclerosis, restoring MBP [ 199 , 200 ]. All these reports confirmed our results that propranolol administration along with cisplatin protects rats’ sensory and motor neuropathy, evidenced by enhancement of MBP expression.…”
Section: Resultsmentioning
confidence: 99%
“…The current treatment for MS is based on three main objectives: the treatment of relapses, symptomatic control, and disease-modifying therapies (DMTs) which primarily target the adaptive immune system. Most of the available therapeutic options are focused on the relapsing-remitting form, while only ocrelizumab (a monoclonal antibody targeting CD20+ B cells) has been approved for the primary progressive disease [75,76].…”
Section: Established Therapies For Multiple Sclerosismentioning
confidence: 99%
“…The development of treatments targeting astrocytes constitutes a key goal of studying astrocytic subsets. In this context, the challenges are to elucidate the role of astrocytes in disease pathogenesis and design disease-specific therapies [75]. The characterization of the heterogeneous astrocyte subgroups, through the identification of sets of characteristic molecular markers for each subgroup, may provide a targeted approach in the pursuit of limiting the neurodegenerative changes associated with CNS inflammation.…”
Section: Astrocyte-selective Therapies: Challenges and Potential Solu...mentioning
confidence: 99%